(untitled) (American Journal of Islam and Society, 2001)
The Ambivalence of the Sacred book attempts to articulate a framework for formulating specific answers, on a case-by-case basis, to three overarching questions pertaining to the seemingly ambivalent relationship between religion and violence. First, it seeks to examine conditions under which religious actors become violent; secondly, the opposite circumstances under which religious actors reject the violence of religious extremists according to the same principles of religious sanctity; and thirdly, the settings in view of which non-violent religious actors can become agents of peacebuilding. The purported goal is to identify and develop means and methods by which religion may become an instrument of conflict management and/or resolution instead of being a source of deadly conflicts. Appleby argues that religion can be administered in such a prudent, selective, and deliberate fashion so as to allow it consistently to contribute to a peaceful resolution of conflicts. Additionally, that a new form of conflict transformation –"religious peacebuilding’- is actually taking shape among local communities plagued with violence. In this sense "ambivalence of the sacred projects an awareness that both possibilities of life and death reside within the holy. The book is divided into two parts. The first part (chs. 1-5) attempts to elaborate elements of a theory of religion’s role in deadly conflict and to address the first two overarching questions above. Citing the cases of South Africa and the transformations in Roman Catholic teachings, in response to both state apartheid violence in the former, and to post-war era pressures for pluralism on the latter, chapter 1 examines the paradoxical and ambivalent logic of the sacred. Chapters 2 and 3 explore the conditions under which religious actors legitimate violence as a sacred duty or privilege in light of the violent forces of ethno-nationalism and religious extremism. Chapter 4 examines the phenomenon of nonviolent religious militancy by looking at Buddhist peacemaking in Southeast Asia and by introducing transnational NGO’s that work with and among local religious actors. The ...